2009
DOI: 10.1007/s11010-009-0276-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of RhoA and FAK induces ERK-mediated osteopontin expression in mechanical force-subjected periodontal ligament fibroblasts

Abstract: The precise mechanism by which Rho kinase translates the mechanical signals into OPN up-regulation in force-exposed fibroblasts has not been elucidated. Human periodontal ligament fibroblasts (hPLFs) were exposed to mechanical force by centrifuging the culture plates at a magnitude of 50 g/cm(2) for 60 min. At various times of the force application, they were processed for analyzing cell viability, trypan blue exclusion, and OPN expression at protein and RNA levels. Cellular mechanism(s) of the force-induced O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 62 publications
3
49
0
Order By: Relevance
“…Mechanically activated ERK1/2 and/or JNK signals are transmitted into the nucleus where they activate the transcription factor AP1 and, thereby, upregulate expression of molecules that are crucial for tissue formation and remodeling, such as type I collagen and osteopontin in bone (Hong et al, 2010;Jeon et al, 2009;Kook et al, 2009). Mechanical strain and distortion of the cell shape also activate membrane-associated phospholipases and, thereby, increase the metabolism of inositol lipids and arachidonic acid in the cytoplasm, which results in the release of Ca 2+ from intracellular stores, activation of protein kinase C (PKC) and the remodeling of cardiomyocytes through activation of mechanosensitive transcription factors, such as EGR1 and AP1 (Fig.…”
Section: Mechanosensitive Transmembrane Receptorsmentioning
confidence: 99%
“…Mechanically activated ERK1/2 and/or JNK signals are transmitted into the nucleus where they activate the transcription factor AP1 and, thereby, upregulate expression of molecules that are crucial for tissue formation and remodeling, such as type I collagen and osteopontin in bone (Hong et al, 2010;Jeon et al, 2009;Kook et al, 2009). Mechanical strain and distortion of the cell shape also activate membrane-associated phospholipases and, thereby, increase the metabolism of inositol lipids and arachidonic acid in the cytoplasm, which results in the release of Ca 2+ from intracellular stores, activation of protein kinase C (PKC) and the remodeling of cardiomyocytes through activation of mechanosensitive transcription factors, such as EGR1 and AP1 (Fig.…”
Section: Mechanosensitive Transmembrane Receptorsmentioning
confidence: 99%
“…It has been suggested that mechanical stress-mediated Rho/ROCK signaling is linked to the expression of a series of osteogenic molecules, such as activator protein-1, osteopontin, and receptor activator of nuclear factor-kappa B ligand, in PDL cells (Kletsas et al 2002;Yamashiro et al 2007;Wongkhantee et al 2008;Hong et al 2010;Pan et al 2014). A better understanding of how PDL cells adapt to the mechanical stress may contribute to the analysis of their osteogenic lineage.…”
Section: Mechanotransductionmentioning
confidence: 99%
“…The direct involvement of MAPKs on mechano transduction has been largely suggested in muscle cells (Li et al, 2000;Zampetaki et al, 2005) and in bone cells (Franceschi and Xiao, 2003;Liedert et al, 2006). In periodontium, centrifugal force during OTM up-regulated COL I expression in human periodontal fibroblasts through the activation of MAPK-AP-1signaling (Kook et al, 2009;Hong et al, 2010). However, little knowledge is available about the mechanism of physiological occlusal force on hPDLCs.…”
mentioning
confidence: 99%
“…Human PDL fibroblasts stimulate osteoclastogenesis in response to compression force through TNF-alpha-mediated activation of CD4 + T cells (Kook et al, 2011b). Osteopontin expression in mechanical force-subjected PDL fibroblasts was activated by the ERK pathway (Hong et al, 2010). The inconsistent findings show that the mechanisms involved in force-applied hPDLCs also depend on the culture conditions and stress regime.…”
mentioning
confidence: 99%